Are early‐life antecedents of suicide mortality associated with psychiatric disorders and suicidal ideation in midlife?. (22nd December 2017) - Geoffroy, M.‐C.; Gunnell, D.; Clark, C.; Power, C.
Abstract : Objective: To establish whether previously identified early‐life antecedents of suicide mortality (i.e. low birthweight, younger maternal age, higher birth order, externalizing problems and adversities) are associated with proximal psychiatric disorders and suicidal ideation, which are themselves associated with an increased risk of suicide. Methods: Participants were from the 1958 British birth‐cohort ( N = 8905) with information on prenatal/childhood experiences and the Clinical Interview Schedule‐Revised at age 45 years. Outcomes were as follows: any internalizing disorder (anxiety disorder/depressive episode), depressive episode, alcohol use disorder and suicidal ideation. Results: After adjustment, higher birth order ( P trend = 0.043), younger maternal age ( P trend = 0.017) and increased number of childhood adversities ( P trend = 0.026) were associated with an increased risk of internalizing disorders. For example, the OR (95% CI) in fourth‐ or later‐born children was 1.48 (1.06–2.07) and for young maternal age (<19 years) was 1.31 (0.89–1.91). Effect sizes were similar in magnitude for depressive episode and suicidal ideation, although associations did not reach conventional significance levels. No associations were found for low birthweight and externalizing problems (in males) and investigated outcomes. Conclusion: Associations for younger maternal age, higher birth order and adversities with adult internalizing disorders suggest that psychiatric disorders may be on the pathway linking some early‐life factors and suicide.